Struktur Komunitas Makrozoobentos di Perairan Morosari, Kecamatan Sayung, Kabupaten Demak - Sulistiyanto, Yuniar Andri; Endrawati, Hadi; Zainuri, Muhammad (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Morosari estuary waters is consist of a pond area which flooded by high tide and became a shallow water area. Makrozoobentos is a biological component, which can be utilized to determine water quality. The purpose of this study is to determine the makrozoobentos community structure in the Morosari waters, Sayung District, Demak. There are 21 spesies of 4 classes, under 3 phyla Mollusca (13 species), consist of Polychaeta (8 species) and Crustacea (2 species), found in the 4 stations in the waters Morosari, District Sayung, Demak. The macrozoobentos abundance values on the entire sample ranged from 9 - 295 ind/m2. The diversity index show a range value from 0,00 – 3,28 (low to high category). The richness index show a range value between 0,00 – 0,94 (small to high category), while the dominance index indicates a range values between 0,18 – 1,00. The water quality show a variation that are still support makrozoobentos life.